2003
DOI: 10.1046/j.0931-1793.2003.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Linguatula serrata Infestation in Stray Dogs of Shahrekord, Iran

Abstract: The present study was undertaken to determine the prevalence of pentastomid parasites in stray dogs between 16 November 2002 and 16 April 2003 in Sahrekord from Chaharmahalobakhtiari province, Iran. A total of 143 stray dogs were shot and the heads were longitudinally sectioned to expose the nasal cavity, and worms, if any, were carefully removed. Adult Linguatula serrata were found in the nasal cavities of 89 (62.2%) dogs. The infestation rate was 67.4 and 53.7% in males and females, respectively. The examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 5 publications
(5 reference statements)
0
29
0
Order By: Relevance
“…The prevalence of linguatulosis in dogs have been determined in different part of Iran, which found to be 76.2 % in Shiraz (Oryan et al 2008), 65.5 % in Shahre-Kord (Meshgi and Asgarian 2003) and 76.47 % in Fars province (Oryan et al 1997). In Bursa, Turkey, 20 % of dogs have been found infected (Akyol et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of linguatulosis in dogs have been determined in different part of Iran, which found to be 76.2 % in Shiraz (Oryan et al 2008), 65.5 % in Shahre-Kord (Meshgi and Asgarian 2003) and 76.47 % in Fars province (Oryan et al 1997). In Bursa, Turkey, 20 % of dogs have been found infected (Akyol et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This parasite has been reported in humans in Iran (Hodjati and naghili 1987;Fata et al 1994, Sadjjadi et al 1998Maleky 2001). Several studies have shown the prevalence of L. serrata infection in animals including, dogs (Oryan et al 1997(Oryan et al , 2008Khalil 1970;Tavassoli et al 2000;Meshgi and Asgarian 2003), camels (Mobedi et al 1998;Oryan et al 1993;Tajik et al 2007;Pourjafar et al 2007;Shakerian et al 2008), buffaloes (Sisakumar et al 2005), sheep (Esmail-Nia et al 2000;Shekarforoush et al 2004;Tavassoli et al 2007;Ravindran et al 2008;NourollahiFard et al 2011), cattle (Nourollahi-Fard et al 2010a) and goats (Saiyari et al 1996;Razavi et al 2004;NourollahiFard et al 2010b). …”
Section: Introductionmentioning
confidence: 99%
“…Infections with L. serrata in human cases have been reported from Africa, South America, Southeast Asia and the Middle East (Beaver et al 1984;El-Hassan et al 1991;Lazo et al 1999;Siavashi et al 2002). Several studies have been conducted on the prevalence of L. serrata in dogs (Tavassoli et al 2007;Meshgi and Asgarian 2003;Oryan et al 2008), camels (Oryan et al 1993;Shakerian et al 2008;Haddadzadeh et al 2009), buffaloes (Tajik et al 2008), goats (Saiyari et al 1996;Razavi et al 2004) and sheep Tavassoli et al 2007). The prevalence rates of 44 % in cattle in Urmia slaughterhouse, Iran (Tajik et al 2006), 19 % in cattle of India (Ravindran et al 2008), 29.9 % in goats in Shiraz, Iran ), have been reported from different countries.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought among some women, that consumption of raw or undercooked liver is helpful for growth of the fetus because of its high content of iron and vitamins. Several studies have been conducted on the prevalence rate of L. serrata in dogs (Tavassoli et al 2007;Meshgi and Asgarian 2003), camels (Oryan et al 1993;Shakerian et al 2008;Haddadzadeh et al 2009), buffaloes (Tajik et al 2008), sheep Tavassoli et al 2007) and goats (Saiyari et al 1996;Razavi et al 2004). Human infection with L. serrata has been reported from different parts of the world including tropical regions of North and South America, Europe, Asia, Africa and Australia (Riley et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…This parasite has also been reported in humans from different regions of Iran (Anaraki Mohammadi et al 2008;Arbabi et al 1996;Maleky 2001;Montazeri et al 1997;Siavashi et al 2002;Sadjjadi et al 1998). Several studies have been conducted on the prevalence rate of L. serrata in dogs (Meshgi and Asgarian 2003;Tavassoli et al 2000), camels (Oryan et al 2008) buffaloes (Tajik et al 2008), sheep, andgoats (Esmail-Nia et al 2000;Shekarforoush and Arzani 2008;Razavi et al 2004). The aim of present study was to determine the prevalence rate of L. serrata nymphs' infestation in liver, mesenteric and MLN in goats that slaughtered at the new industrial slaughterhouse, Tabriz, Iran.…”
Section: Introductionmentioning
confidence: 99%